Cost Comparison between RCC and Load Bearing Earthquake Resistant Residential Building in Terai Region - Gyawali, S.; Gyawali, B. R.; Adhikari, R.; Shrestha, S. P. (Journal of Lumbini Engineering College, 2024)
This study compares the cost-effectiveness of earthquake-resistant residential construction methods, focusing on RCC framed structures and load-bearing construction in Kanchan Rural Municipality, Rupandehi. Utilizing designs from the NRA design catalogue Volume-I, load-bearing designs were referenced, while RCC framed building designs were intentionally aligned with identical architectural plans, district rate and DUDBC norms for cost estimate, NBC Code 202 and 205 to show the features of earthquake resistant load bearing building and RCC building respectively. The analysis of Load Bearing and RCC framed buildings reveals a consistent trend where an increase in total area is associated with a rise in total construction cost. Interestingly, as the building size increases, there is a corresponding decrease in the cost per square foot. RCC framed structures assign a higher percentage to concrete work and lower weightage to brickwork compared to Load-Bearing buildings. In all building types, reinforced cement concrete construction is found to be costlier than load-bearing construction. An in-depth analysis has been conducted to examine the incremental costs associated with RCC construction compared to load-bearing construction across various house types, categorized by the number of stories. The findings provide valuable insights into the variations in RCC costs based on the number of stories, offering essential information for informed decision-making in construction methods and expenses.